Economic Impact of Farmer Producer Company on its Members: A Case of Belauri Municipality - Deore, Pradnyesh; M. K. Rathod,; Shelake, Chhakuli (Journal of Agricultural Extension Management, 2022)
The present study on the economic impact of Farmer Producer Company on its members was undertaken in Nashik district of North-Western region of Maharashtra state with a sample size of 120 respondents from two Farmer Producer Companies. To study the economic impact, mean and per cent change was calculated out of pre and post participation of members. This per cent change was then considered for the extent of the impact of each parameter. As regards the impact on economic status changes observed were, in employment generation which was 52.25 per cent and 'Z' value (9.58), in subsidiary occupation it was 43.12 per cent and 'Z' value (9.46), in annual income 61.27 per cent and 'Z' value (9.75), in annual expenditure 40.00 per cent and 'Z' value (7.24), and the change in annual savings was 81.56 per cent and 'Z' value (10.54). The overall mean economic impact of Farmer Producer Company on its members, pre and post participation was 55.64 per cent.